Two new species of Heissothignus from New Guinea (Heteroptera: Lygaeoidea: Heterogastridae) - Brailovsky, Harry (Zootaxa, 2011)
Two new species Heissothignus slateri and Heissothignus baitetus from New Guinea are described, illustrated, and included in the family Heterogastridae (Lygaeoidea). A key to the known species of Heissothignus is presented.